Leading‐Edge Pulmonary Gene Therapy Approached by Barrier‐Permeable Delivery System: A Concise Review on Peptide System. Issue 12 (28th October 2022) - Chen, Dinghao; Kong, Nan; Wang, Huaimin
Abstract : The lack of effective treatments for pulmonary diseases poses a global health burden. The direct local gene therapy serves as one of the alternative administrations to treat pulmonary diseases. Compared with the conventional viral/nonviral system, the peptide–vector‐mediated in vivo lung gene therapies exhibit various benefits. However, the related clinical trials are still in their infancy. The major obstacle to the pulmonary delivery of gene cargoes may be the barriers from various extracellular mucosal layers and intracellular membranes. This review highlights the recent development of peptide‐based gene delivery systems and their applications. The peptide designing rules for the barrier‐permeable pulmonary gene delivery are described first. After briefly summarizing how oligopeptides facilitate the local gene therapy in lung tissue with the focus on cell‐penetrating peptides, the local delivery system of the polypeptide and several alternative hybridizing systems of the peptide with other types of materials are discussed. Finally, the blueprint and the remaining challenges in peptide designations are discussed before they enter into the real translation process. Abstract : Herein, the recent developments of peptide‐based gene delivery systems and their applications are described, which cover the peptide design principle, oligopeptides and polypeptides, and hybrid systems for gene delivery.